Tuning of photoluminescence behavior of gold coated chitosan-polyvinyl alcohol binding with graphene quantum dots. (2022) - Salunke, Amol S.; Salunke, Shrikrishna T.; Deokate, Ramesh J.; Kale, Bharat B.
Abstract: In this work, Gold coated Chitosan-Polyvinyl Alcohol binding with Graphene Quantum Dots (Au/CTS/PVA/GQDs) nanoparticles were reported by chemical reduction method. The Au/CTS/PVA/GQDs nanocomposite prepared with various reaction duration further used for physiochemical study. The Fourier Transformation Infrared Spectroscopy (FTIR) and the UV–Vis spectrophotometer were used for further analysis. The FTIR study revealed the hydrogen bonding interaction between PVA polymer and GQDs nanoparticles. In optical properties, photoluminescence study presented blue shift effect for the different reaction time duration. The average size of the nanocomposites was measured by DLS data, and nanoparticle size decreased between 172.2 nm and 134.8 nm with reaction time.